Knowledge, Attitude and Practice towards Religious Obligations among Healthcare Workers in Hospital Langkawi, Malaysia - J, Hafiz; MR, Dzulkhairi; MA, Shamsir; N, Abu (IIUM Medical Journal Malaysia, 2016)
Introduction: Islamic prayers involve certain physical movements and positions. These positions may be difficult to achieve in Muslim patients who suffer from any illness that limit their physical movements. Therefore, Islam introduced the concept of Rukhsah or exemptions. The objective of this study was to assess the knowledge, attitudes and practices of healthcare workers related to performing prayers during illness. Materials and Methods: A cross sectional study was conducted among 121 healthcare workers in Hospital Langkawi, between 22nd to 24th April 2014. Simple random sampling method was used to select the participants among healthcare workers in Hospital Langkawi to attend a workshop on Rukhsah Ibadah. The participants were given a set of questionnaire to answer and all the data were collected just before the talk began. Results: The majority of the participants 108 (89.3%) were female and more than half of them 74 (61.2%) were staff nurses. The mean age for the participants was 32.4 (SD: 9.42) years. About 73 (60.3%) of the participants have good knowledge, 62 (51.2%) have good attitude and 73 (60.3%) have good practice towards religious obligations and Rukhsah. Bivariate analysis shows no correlation between age and knowledge, attitude and practice score. There was also no correlation seen between knowledge, attitude and practice score. Conclusion: Almost half of the participants have good knowledge, attitude and practice on performing prayers during illness. By conducting proper training and coaching, it is hoped that their level of understanding towards Rukhsah can be improved.